Pengaruh Beban Kerja dan Stres Kerja Terhadap Kinerja Pegawai pada PT. Andika tama - Jaka Santosa (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This research employs a quantitative methodology to analyze the impact of workload and work stress on employee performance. The study population consists of employees from relevant institutions, with a saturated sampling technique applied—resulting in a total sample size of 45, representing the entire population. Data analysis was performed using SPSS 25, including classical assumption testing. The findings indicate that, partially, workload (X1) does not significantly affect performance, leading to the acceptance of the null hypothesis (H₀) and rejection of the alternative hypothesis (Hₐ). In contrast, work stress (X2) exhibits a significant negative partial effect, supported by a t-value of -3.417 exceeding the critical value of -1.682 and a significance level of 0.001 < 0.05, resulting in the rejection of H₀ and acceptance of Hₐ. Furthermore, simultaneously, both workload and work stress demonstrate a significant combined influence on employee performance, as evidenced by an F-value of 5.928 > 3.220 and a significance value of 0.005 < 0.05.